Pengembangan Bahan Ajar Literasi Digital Terintegrasi dengan Kearifan Lokal Dalam Membentuk Karakter Siswa - Fathurrahman, Fathurrahman; Irawan, Bambang (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2025)
This research is used as an initial basis in developing teaching materials that aim to identify real needs in the field related to learning materials, so that quality and appropriate teaching materials can be produced. One of the local wisdom values raised in this development is the Maja Labo Dahu Tradition from the Bima Region. This research aims to identify the needs of local history-based teaching materials as a basis for developing learning materials that are effective and relevant to the local cultural context. The main focus of the development of this teaching material is the integration of local wisdom values, especially the traditions of the people of Bima. The research method used was descriptive qualitative method, with data collection through observation, interviews, and documentation studies at several senior high schools (SMA/SMK) in the relevant region. The results showed that there is a high need for teaching materials that promote local history and culture. This condition encourages the need to develop digital literacy-based teaching materials that contain local wisdom values, in order to increase students' understanding of regional history and strengthen cultural identity in the school environment.